2001
DOI: 10.1016/s0886-3350(01)00891-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heparin surface modification in reducing silicone oil adherence to various intraocular lenses

Abstract: Intraocular lenses with a hydrophilic optic have less tendency toward adherence to silicone oil than more hydrophobic designs. A foldable silicone IOL with heparin surface modification can significantly reduce potential silicone oil adherence, comparable to the level achievable with the rigid HSM PMMA designs. Two new foldable IOL styles, the HSM silicone IOL and IOLs in the general class of hydrophilic-acrylic, were highly efficacious in reducing silicone oil adherence. There is now a real choice of foldable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 33 publications
0
28
0
2
Order By: Relevance
“…33 This phenomenon might be explained by the fact that coating of PMMA IOLs with heparin converts their hydrophobic surface into a hydrophilic one. Studies from our laboratory 34,35 have reported that the interaction of silicone oil with a silicone IOL is dramatically decreased if the latter is surface modified with heparin ( Figure 2a and b). Its hydrophilic chains bound to the surface of the IOL extend into the aqueous media and form a highly hydrated layer around the lens by trapping water molecules.…”
Section: Silicone Oil Interaction With Different Iol Materialsmentioning
confidence: 98%
See 1 more Smart Citation
“…33 This phenomenon might be explained by the fact that coating of PMMA IOLs with heparin converts their hydrophobic surface into a hydrophilic one. Studies from our laboratory 34,35 have reported that the interaction of silicone oil with a silicone IOL is dramatically decreased if the latter is surface modified with heparin ( Figure 2a and b). Its hydrophilic chains bound to the surface of the IOL extend into the aqueous media and form a highly hydrated layer around the lens by trapping water molecules.…”
Section: Silicone Oil Interaction With Different Iol Materialsmentioning
confidence: 98%
“…[30][31][32][33][34][35] Apple and associates 30,31,34,35 in three different studies have compared the degree of silicone oil adherence occurring with several IOLs fabricated from various biomaterials. These studies from our laboratory have demonstrated that the more hydrophobic materials with higher dispersive energy and relatively higher contact angles had more silicone oil adherence.…”
Section: Silicone Oil Interaction With Different Iol Materialsmentioning
confidence: 99%
“…Recently, Arthur et al [19]investigated the effect of heparin surface modification (HSM) and silicone oil (AdatoSil 5000, Escalon Ophthalmic) adherence to various IOLs. The mean silicone oil coverage of the hydrophilic acrylic IOLs (Centerflex 600H, Rayner) was 5.6 ± 2.5%; of the HSM PMMA IOLs (CeeOn 811) it was 6.2 ± 4.3%; of the HSM silicone optic IOLs (CeeOn Edge 911), 6.7 ± 3.2%, and of the standard PMMA IOLs (CeeOn Edge 809A), 20.3 ± 13.3%.…”
Section: Discussionmentioning
confidence: 99%
“…In several clinical and experimental studies, the interaction of silicone oil with various IOLs has been investigated [19, 20, 21, 22, 23]. In most of these studies, one type of silicone oil was used.…”
Section: Introductionmentioning
confidence: 99%
“…25 Optic diameter is also known to influence the formation of PCO, the incidence being lower in IOLs with larger optic diameter.…”
Section: 2324mentioning
confidence: 99%